Contract farming for improving smallholder incomes: What can we learn from effectiveness studies? - Ton, Giel; Vellema, Wytse; Desiere, Sam; Weituschat, Sophia; D'Haese, Marijke (World Development, 2018)
Contract farming is a sales arrangement between a farmer and a firm, agreed before production begins, which provides the farmer with resources or services. Many governments and donors promote contract farming as part of agricultural development policies. However, there is serious concern whether smaller farmers can benefit from these arrangements. This paper presents the results of a systematic review that analysed the evidence in the literature on income effects for smallholders. The review included all studies with an econometric design to reduce selection bias in effect estimates. The meta-analysis covered 26 empirical instances of contract farming in 13 developing countries. The contracts varied widely, with varying service packages provided by the firm to the farmers. Using truth table analysis, we explored combinations of services associated with relatively high or relatively low income effects. The meta-analysis resulted in an overall pooled average effect size of 38%. However, we show that there are publication and survivor biases. Non-significant effects are systematically underreported. Moreover, all studies assessed the effectiveness of the contractual arrangement when these had already survived the start-up problems. Both sources of bias lead to an overestimation of the average income effect. The findings point to the need for substantial income effects for contract farming arrangements to survive over time. Both firms and farmers face risks; for example, farmers may side-sell products after having received the services from the firm. The most effective contractual arrangements included a price premium, especially when there was no farmers’ organisation to broker the contract between the farmer and the firm. We show that smallholders can benefit from the contractual arrangement. However, the poorest farmers are rarely included; we show that, in 61% of the cases, the contract farmers had significantly larger landholdings or more assets than the average farmers in the region.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture - agricultural markets / agricultura - mercados agrícolos; agriculture / agricultura

Mozambique plantation leaves no land or jobs for villagers - Adler, Nils (New Internationalist, 2018)
In northern Mozambique, villagers were promised jobs to replace land taken for forestry. Five years later, they’re still waiting, discovers Nils Adler.
Keywords: #Reporting & Media / Reportagem & Mídia; *indexed; *tagged; DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; GD - Lichinga; GP - Niassa; L - english / inglês; agriculture / agricultura; governance / governação; land governance / gestão de terra; private sector / setor privado

Strong but not Broadly Shared Growth. Mozambique Poverty Assessment - World Bank (World Bank, 2018)
Mozambique has recorded strong growth, but many low-income households are missing out on the benefits and policy options to make rowth more inclusive in Mozambique
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura; poverty / pobreza